Delay in school project in Lembah Klang / Hasniza Md. Kasa - Md. Kasa, Hasniza (2005)
A construction organization is an organization that often has to face more crises as compared to other industries. This is due to the problems of securing projects, organization to other industries. This is due to the problems of securing projects, organization and construction, and lack of sources of materials that usually occurred during peak construction periods. In minimizing the extension of time and delay project, the needs of efficient methods and approaches must be used in construction organization so as to avoid critical problems. The construction industry in Malaysia as in any other country is an enabling industry to other economy is sustained by demands derived from other sectors of the economy. In this context government policies can only be effectively and efficiently executed if the interfacing construction phase is an efficient and effective enabler. Delay is the most common and costly problem encountered on construction project.